[ENV03]Equilibrium Adsorption Study Of 3-Chlorophenol And O-cresol On Modified Mantmorillonite. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (2004)
Phenolic compounds are commonly produced in wastewater streams generated by petrochemical, oil refineries, coal conversion,steel plant, paint and phenol-producing industries (Gallego et al., 2003; Aygunn et al.,2003).